ANALISIS PENGARUH MANAJEMEN KONFLIK TERHADAP EFEKTIVITAS PENGELOLAAN SD DI KAB. KUTAI KARTANEGARA - Nur Agus Salim; Jafar Haruna; Saraka Saraka (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2017)
This research aims to find out the description of conflict management of teachers and principals at primary schools in Kutai Kartanegara and to find out whether conflict management affects the effectiveness of school management. The research method used is quantitative approach. Data collection techniques used questionnaires and data analysis techniques using descriptive and inferential statistics. From result of hypothesis test that there is a significant and positive influence between managerial ability to school management effectiveness with Fcount test result 78,794> 3,875 Ftabel with sig = 0,000 <5% this means linear regression model can be used to predict influence of conflict management to effectiveness of school management. Result of determinant test 0,220 can be interpreted that equal to 22,0% effectiveness variable can be influenced by conflict management variable and the rest influenced other variable not examined in this research. Based on the result of instrument score of variables of conflict management, the distribution is in the medium category and based on inferential test can be concluded that conflict management has a significant positive effect on the effectiveness of school management.